A new simple method to measure wall thermal transmittance in situ and its adaptability analysis. (25th July 2017) - Meng, Xi; Luo, Tao; Gao, Yanna; Zhang, Lili; Shen, Qiong; Long, Enshen
Highlights: The formation mechanism of the 1-D heat transfer zone is studied with locally heated. Influence degree of temperature difference is researched on the test accuracy. A regression equation can be obtained on the box minimum dimension. This paper lays a solid foundation for application and generalization of the SHB-HFM. Abstract: The Simple Hot Box - Heat Flow Meter Method is proposed to measure the wall thermal transmittance conveniently in situ with the high accuracy on the basis of the previous study, while it avoids the heavy equipment of the Hot Box Method and overcomes outdoor and indoor thermal environment limitation of the Heat Flow Meter Method. According to these, this study mainly analyzed the determination method of the hot box dimension and the effect of the heating temperature by the numerical simulation. Results shows due to the local heating from the hot box, the wall can be divided to four zones with the different thermal characteristics, where a one-dimensional heat transfer zone is the optimum one to past the thermocouples and heat flow meters. With increasing the hot box dimension, the one-dimensional heat transfer zone increases linearly and the heat dissipation zone is constant, defining the minimum hot box dimension. The minimum dimension increases linearly with increasing the wall thickness or equivalent thermal conductivity. When temperature difference is more than 20 °C, its effect can be ignored on the minimum dimension. And the maximum system error decreases by up to 4.4–7.5% with the temperature difference increasement from 10 °C to 30 °C. Taking wall thickness, wall equivalent thermal conductivity, temperature difference as variables, a regression formula is obtained to determine the minimum box dimension and the recommended values of the hot box dimension are also offered.